Global-scale processes and effects of magnetic reconnection on the geospace environment - Fuselier,SA; Petrinec,SM; Reiff,PH; Birn,J; Baker,DN; Cohen,IJ; Nakamura,R; Sitnov,MI; Stephens,GK; Hwang,J; Lavraud,B; Moore,TE; et al. (Space Science Reviews, 2024)
Recent multi-point measurements, in particular from the Magnetospheric Multiscale (MMS)spacecraft, have advanced the understanding of micro-scale aspects of magnetic reconnection. In addition, the MMS mission, as part of the Heliospheric System Observatory, combined with recent advances in global magnetospheric modeling, have furthered the understanding of meso- and global-scale structure and consequences of reconnection. Magneticreconnection at the dayside magnetopause and in the magnetotail are the drivers of the globalDungey cycle, a classical picture of global magnetospheric circulation. Some recent advances in the global structure and consequences of reconnection that are addressed hereinclude a detailed understanding of the location and steadiness of reconnection at the dayside magnetopause, the importance of multiple plasma sources in the global circulation, andreconnection consequences in the magnetotail. These advances notwithstanding, there areimportant questions about global reconnection that remain. These questions focus on howmultiple reconnection and reconnection variability fit into and complicate the Dungey Cyclepicture of global magnetospheric circulation.